Effect of Formulated Fertilization on Fruit Quality of Early Ripe Peach - Pu Changbing; Xiao Qiao; Wang Jin; Liang Dong; Lv Xiulan (E3S Web of Conferences, 2019)
Using the early maturing peach variety 'Japan Matsusen' as the test material, nine groups of formula fertilization schemes were set up by orthogonal experiment to study the effects of different fertilization treatments on the quality of peach fruit, in order to obtain the best fertilization formula to improve fruit quality. The results showed that the quality of peach fruit was significantly improved by adding organic fertilizer to the base fertilizer instead of chemical fertilizer. Therefore, by adding organic fertilizer as the base fertilizer, reducing the application amount of chemical fertilizer, and adding other trace element fertilizers can effectively improve the quality of peach fruit.